Academic Stress — Analysis and Measures - Tandon, Tanu (THE PRIMARY TEACHER, 2017)
Stress refers to the way the mind and body respond to physical and emotional stressors. Continued exposure to such stressors may lead to mental problems like anxiety, depression, anger and frustration, and even develop suicidal tendencies (as seen in a few cases), apart from causing health disorders and fatigue. One, often, hears of students, functioning under extreme stressful conditions. Academic or educational stress is one of the most common problems affecting students. It, therefore, becomes imperative to identify the sources of academic stress and its adverse effects on students. This paper discusses these issues and suggests ways through which learning may be made stress free and fun.